Labor demand and unequal payment: Does wage inequality matter? Analyzing the influence of intra-firm wage dispersion on labor demand with German employer-employee data - Arnd Kölling (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This paper examines the relationship between intra-firm wage dispersion and establishments' employment in a theoretical analysis and empirical regressions using German "Linked Employer-Employee Data from the IAB" (LIAB) for the years of 1996 through 2008. Therefore, fractional probit models for the panel data, recommended in Papke and Wooldridge (2008), and fixed effects regression with a log-odds transformation of the dependent variable are conducted to estimate share equations of a labor demand model. The results illustrate a negative influence of the residual wage inequality that takes into account the composition of the workforce in the establishment with employment. In addition, an increasing wage dispersion at the lower end of the wage distribution decreases labor demand of the establishment but the estimates of the overall wage dispersion becomes insignificant then.
Keywords: J23; J21; E24; 330; Labor Demand; Wage Dispersion; Share Equation